Perancangan Alat Pemberi Pakan Ikan Otomatis Menggunakan Arduino Berbasis Android (Studi Kasus : Toko Arapaima Aquarium) - Hendra; Andhika (Jurnal KomtekInfo, 2020)
Feeding fish is the most important thing in raising fish, with regular feeding to fish the fish will be able to continue to breed, In general, the process of feeding still requires human resources that are still manual, so that it will be difficult and disrupt human activity itself, if the process carried out must spread the food in the aquarium when someone is not in place, Therefore, currently IOT (Internet of Thing) technology has been developed which can facilitate human activities with remote control systems. The process of feeding with a remote control system is done using android, so as to simplify and save someone's time in the process of feeding without having to be in place. The control system used is Arduino ESP8266 as a single board micro controller platform, so that the control device can function to connect the WI-FI network. The process of connecting an Arduino ESP8266 device with a smartphone is done using the broker as hosting, the broker used was MQTT (Message Queuing Telemetry Transport), MQTT is a protocol that runs on the TCP / IP stack and is designed specifically for machine to machine that does not have a specific address. MQTT broker's working system is to implement publish as data sender, subcribe as data recipient, and topic as hosting data broker.